Pengaruh Permainan Happy Jump Challenge Terhadap Kemampuan Membedakan Perilaku Baik dan Buruk Anak Usia Dini - Heri Hidayat; Fadilah Ersa Rania; Soniah Natalia; Sofie Qanita Rahma; Jordan Moharnika; Fadilla Ayuningtyas (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Many children aged 5–6 struggle to distinguish between good and bad behavior due to unappealing conventional learning methods. This study aims to determine the effect of the Happy Jump Challenge game on the ability to differentiate these behaviors among early childhood students at PAUD Nurul Ikhlas, Bandung. The Happy Jump Challenge is an educational, physical-manipulative game using picture cards and a response board to help children categorize moral behaviors enjoyably. This quantitative study employed a one-group pretest-posttest quasi-experimental design with 16 children aged 5–6 years selected through total sampling. Data were collected via structured observations using an 8-item instrument on a 1–4 developmental scale (BB, MB, BSH, BSB). The tool was validated using Pearson Product Moment (r = 0,755-0,894) and Cronbach’s Alpha 0,89. Data analysis involved Chi-Square (normality), F-test (homogeneity), and a Paired Sample t-test. The results showed that both datasets were normally distributed and homogeneous. The mean score increased significantly by 10.31 points, from the pre-test (x̄ = 20,19) to the post-test (x̄ = 30,50). The Paired Sample t-test yielded a calculated t-value (20,122) > t-tabel (2,947) at α = 0,01, rejecting H0. Ultimately, all 16 children achieved the highest developmental category on the post-test. These findings demonstrate that the Happy Jump Challenge significantly improves children's ability to distinguish between good and bad behavior, making it a highly recommended innovative tool for early childhood moral education